Corporate failure prediction of public listed companies in Sarawak - Liu, Boon Hui (Universiti Malaysia Sarawak (UNIMAS), 2012)
The purpose of this research is to extent the bankruptcy prediction model to predict financial distress among 25 public listed companies in Sarawak from period 2006 to 2010 by using secondary data. Applicability of Altman Z-Score Models was used to identify classification on three main zone which is safe, grey or distress zone.